Cost Minimization Analysis (CMA) Penggunaan Obat Captopril dan Lisinopril pada Pasien Hipertensi di RSUD Sultan Suriansyah Banjarmasin: Cost Minimization Analysis (CMA) Use of Captopril and Lisinopril Drugs in Hypertensive Patients at Sultan Suriansyah Hospital Banjarmasin - Nailul Muna; Melviani Melviani; Erlina Syamsu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Hypertension is a world health problem leading to increased morbidity and mortality, as well as burdening the cost of health services, including in Indonesia. Cost Minimal hypertension treatment can reduce the high incidence of hypertension. The purpose of this study was to determine the cost that is more cost-minimize among the use of captopril and lisinopril in outpatient hypertension patients at Sultan Suriansyah Hospital Banjarmasin. This study is an analytic with a design cross sectional. Data collection is done by looking at the medical records of hypertensive patients outpatient hospital Sultan Suriansyah Banjarmasin who received antihypertensive therapy captopril and lisinopril. The sampling method used is non-probability sampling by using the technique purposive non-random sampling. Samples that 35 patients were used. The cost component measured is direct medical costs outpatient hypertensive patients which includes the cost of antihypertensive drugs, the cost of disease drugs participants, laboratory fees, and consulting fees. The results showed that the average total direct medical cost in the captopril group was Rp127.886 and the group lisinopril Rp.274.971. In the captopril group it has a more minimal cost compared with the lisinopril group.